Beverage patterns, blood pressure, and proteinuria among West Africans with chronic kidney disease: a cross-sectional analysis of the diet, CKD, and apolipoprotein L1 study - Djelmami-Hani, Rayan; Adebile, Tolulope; Zhao, Runqi; Kwakyi, Edward; Amira, Oluwatoyin; Omotoso, Bolanle; Mamven, Manmak; Raji, Yemi Raheem; Solarin, Adaobi; Umeizudike, Theophilus; Eduful, Ernestina; Olokode, Bola Fatima; et al. (Frontiers in Nutrition, 2026)
IntroductionBeverage intake is an important yet understudied contributor to blood pressure (BP) and proteinuria. This is particularly relevant in sub-Saharan Africa, where rapid shifts toward sugar-sweetened beverages (SSBs) and ultra-processed beverages, driven by affordability and aggressive marketing, are occurring alongside a high burden of Chronic Kidney Disease (CKD) within resource-limited health systems. Additionally, there are cultural differences within African populations that make beverage patterns in sub-Saharan Africa differ across populations and from Western cultures.MethodsWe conducted a cross-sectional analysis of 494 participants in the Diet, CKD, and APOL1 (DCA) Study cohort in West Africa. We assessed beverage consumption from 24-h dietary recalls and patterns using principal component analysis. We analyzed associations of beverage patterns with systolic BP (SBP), diastolic BP (DBP), and proteinuria using univariate and multivariable linear mixed-effects regression models. We adjusted for covariates, such as clinical site (random effect), socio-demographic factors, and lifestyle factors.ResultsWe identified 4 unique beverage patterns: (i) SSB and Alcohol, (ii) Milk and Alcohol, (iii) SSB and Water without Alcohol, and (iv) Milk and Milk Products. No beverage patterns showed consistent association with SBP or DBP, and sensitivity analyses of individual beverages yielded null findings. In adjusted analyses, the Milk and Milk Products beverage pattern showed a positive association with SBP (Tertile 2 vs. 1: β = 5.61 mm Hg; 95% CI: 1.54–9.57) and a directionally consistent but not significant association in tertile 3 vs. tertile 1. An exploratory interaction suggested a stronger positive association of this pattern with SBP among individuals with diabetes.ConclusionThe Milk and Milk Products beverage pattern may be associated with higher SBP in adults with CKD in West Africa, with a potentially stronger association among those with diabetes. Given that no associations remained significant after false discovery rate correction, these findings should be interpreted cautiously. Future studies are needed to confirm these findings and clarify their long-term implications for kidney and cardiovascular health.